2016
DOI: 10.1097/spv.0000000000000306
|View full text |Cite
|
Sign up to set email alerts
|

Subjective and Objective Outcomes of Robotic and Vaginal High Uterosacral Ligament Suspension

Abstract: These short-term outcomes are promising and show a high success rate for the uterosacral ligament suspension at the time of a hysterectomy regardless of whether it was performed vaginally or robotically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…In their study, Davila et al reported that none of the 5 patients treated with robotic‐assisted laparoscopic single‐site uterosacral ligament suspension developed de novo SUI after the procedure. Similarly, a retrospective study by Vallabh‐Patel et al found no new cases of onset of stress or urge urinary incontinence in the RALUSLS group, whereas 1 patient had occult SUI on urodynamic testing.…”
Section: Discussionmentioning
confidence: 83%
“…In their study, Davila et al reported that none of the 5 patients treated with robotic‐assisted laparoscopic single‐site uterosacral ligament suspension developed de novo SUI after the procedure. Similarly, a retrospective study by Vallabh‐Patel et al found no new cases of onset of stress or urge urinary incontinence in the RALUSLS group, whereas 1 patient had occult SUI on urodynamic testing.…”
Section: Discussionmentioning
confidence: 83%
“…The 3 criteria proposed by Vallabh-Patel et al (9) were adopted for RPS: (I) the distance between the most distal end of the prolapsed anterior or posterior vaginal wall and the hymen was ≤0 cm, and descent of vaginal vault was ≤1/2 the full length of the vagina; (II) it was determined that the related symptoms of POP had disappeared according to the third question in Pelvic Floor Distress Inventory-Short Form 20 (PFDI-20) ("Do you often see or feel a vaginal mass protruding? "); (III) no surgery or pessary treatment was performed for the prolapse.…”
Section: Criteria For Successful Surgerymentioning
confidence: 99%
“…We adopted the criteria for successful surgery proposed by Vallabh-Patel et al (8), including (I) ≤0 cm prolapse for the leading edge and prolapse ≤1/2 of the total vaginal length from the vaginal vault; (II) absence of related POP symptoms as reported on the third question of our survey ("Do you usually have a bulge or something falling from your vaginal area that you can see or feel? "), of the pelvic floor distress inventory-short form 20 (PFDI-20); and (III) neither prolapse re-operation nor pessary use.…”
Section: Follow-up and Evaluationmentioning
confidence: 99%
“…Of the 84 POP patients, the median age was 59 (range, 38-87) years; the median body mass index (BMI) was 23.4 (17.0-34.8) kg/m 2 ; and the median numbers for pregnancies and births were 3 [1][2][3][4][5][6][7][8] and 2 [1][2][3][4][5][6][7][8], respectively. None of the patients had a history of hormone replacement therapy, and there were 59 cases (70%, 59/84) of menopause.…”
Section: Patientsmentioning
confidence: 99%